Factors Associated with the Uptake OF Cervical Cancer Screening Among HIV-Positive Women Attending Immune Suppressed Syndrome Clinic at Mbarara Regional Referral Hospital - Kavira, Victoria; Archibong, Victor; Ayuba, John Tabakwot; Usman, Ibe Michael; Tibaijuka, Leevan; Owaraganise, Asiphas; Ngonzi, Joseph (Reserach square, 2023)
Purpose: This study determined the prevalence of precancerous cervical lesions, uptake of cervical cancer screening (CCS), and its associated factors among HIV-positive women attending the Immuno-Suppression Syndrome (ISS), and the Colposcopy and Cervical Pathology Clinics of Mbarara Regional Referral Hospital (MRRH). Patients and methods: This were a cross-sectional study conducted at the ISS Clinic of MRRH, southwestern Uganda. Data were collected using semi-structured questionnaires among 303 confirmed HIV-positive patients between January 2020 and April 2020. Descriptive, bivariate, and multivariate analyses were conducted. Results: The majority of the respondent 179(59.1%) had screened for cervical cancer and of the 124 unscreened women, 5(4.0%) had precancerous cervical lesions. HIV-positive women directed by healthcare staff in their most recent visit (AOR = 7.7, 95%CI: 4.08–14.63, p < 0.01), women from villages where outreaches were conducted (AOR = 4.4, 95%CI: 1.94–10.05, p < 0.01), and women that were attended to by two skilled health workers (AOR = 5.1, 95%CI: 1.81–14.43, p < 0.01) were more likely to go for CCS. Conclusion: The uptake of CCS services among HIV-positive women attending ISS clinic was generally high. The prevalence of precancerous cervical lesions was generally low. This study demonstrates that referrals, outreaches, and the presence of skilled health workers enhanced the uptake of cervical cancer screening among HIV-positive women attending the ISS clinic at Mbarara Regional Referral Hospital.
Keywords: Cervical cancer screening; Immune Suppressed Syndrome; HIV patients